Topical platelets rich plasma implications in management of burn - El Ghazaly, Mohammed A.; Abo Grida, Hisham S.; El Sheikh, Yasser M.; Aly, Medhat S. (International Surgery Journal, 2019)
Background: Burn injury is a major cause of trauma to the human body, causing death and disability with a long healing period and high health care costs. The mortality rate of burn injury is decreasing with new treatment modalities. Methods: Fifty patients who underwent to use or not use the platelet rich plasma (PRP) technique in improving the process of healing in burn scars and graft either by physiological dressing or sub dermal injection between 2 groups. The study was conducted on patients presented to Plastic and Reconstructive Surgery Department of Abou Qir General Hospital and Menuofia University in the period from October 2017 to October 2018. Results: On treating the burned area with PRP injection and conventional dressing, the minimal time taken for complete healing was 10 days, while the maximal time taken was 24 days with median 18 days while on treating the burned area with conventional dressing without PRP injection, the minimal time taken for complete healing was 14 days, while the maximum time taken was 32 days. Conclusions: With application of PRP decreased the need of grafting through promoting the healing process of the wound of burned areas than areas not applied with PRP.